Boy Melodrama: Genre Negotiations and Gender-Bending in the Supernatural Series - Łuksza, Agata (Text Matters: A Journal of Literature, Theory and Culture, 2016)
For years Supernatural (CW, 2005–) has gained the status of a cult series as well as one of the most passionate and devoted fandoms that has ever emerged. Even though the main concept of the series indicates that Supernatural should appeal predominantly to young male viewers, in fact, the fandom is dominated by young women who are the target audience of the CW network. My research is couched in fan studies and audience studies methodological perspectives as it is impossible to understand the phenomenon of Supernatural without referring to its fandom and fan practices. However, it focuses on the series’ structure in order to explain how this structure enables Supernatural’s viewers to challenge and revise prevailing gender roles. Supernatural combines elements of divergent TV genres, traditionally associated with either male or female audiences. It opens up to gender hybridity through genre hybridity: by interweaving melodrama with horror and other “masculine” genres the show provides a fascinating example of Gothic television which questions any simplistic gender identifications.